Forced housing mobility and mental wellbeing: evidence from Australia. Issue 1 (2nd January 2023) - Ong ViforJ, Rachel; Hewton, Jack; Bawa, Sherry; Singh, Ranjodh
Abstract: This article examines the links between forced housing mobility and the mental wellbeing of Australians in an era of heightened risks in both labour and housing markets. Specifically, we examine how the links between forced housing mobility and mental wellbeing may vary according to states of employment and housing tenure insecurity. Using the 2001–2018 Household, Income and Labour Dynamics in Australia Survey, we implement hybrid models across four mental wellbeing dimensions and uncover three key findings. First, there is strong evidence that forced moves impair mental wellbeing. Second, the adverse wellbeing impacts of forced moves are greater for those experiencing employment insecurity than those in secure employment. Third, forced moves can depress the wellbeing of both owner purchasers and private renters, but the wellbeing penalty is greater in the case of the former. Overall, our analysis emphasises the importance of harnessing housing as a policy instrument for promoting wellbeing. Our findings also highlight the need for policies that mitigate loss of home ownership and reforms that improve tenure security for renters.